Культурное развитие Костанайского региона в 1960-е годы (по данным местной периодики) - Ерёменко, А.В. (My University, 2013)
This article is about cultural life of Kostanay region in 1960. It relies on the datum of local periodic. The content of this investigation includes the development of amateur talent groups, arts and crafts, painting, theatre, cinematography and others.